The Influences of Female Directors on Financial and Non-Financial Performance of Chinese Publicly Listed Companies - SONG, MING (2019)
This study examines the influences of female directors on performance of Chinese companies. Both financial and non-financial performance are evaluated. Female chairman is used as the proxy for female directors. Based on a sample of 1,325 Chinese publicly listed companies from 2014 and 2018, this study finds out that female chairmen are related to lower stock returns, lower risks, slightly higher efficiency, better corporate governance, worse corporate social responsibility commitment, and higher pay gap inside the companies. Meanwhile, none of the common company-specific characteristics (i.e. leverage) is significant determinants of appointment of female chairmen. Overall, this study finds out that companies with female chairmen generally under perform companies with male chairmen. However, it is unfair to attribute the under performance of these companies solely to female chairmen. Specifically, troubled companies are more likely to appoint female chairman. This is called “glass cliff” effects. Therefore, future studies should take account of “glass cliff” effect in analysis of influences of female directors.